Creating Websites In Hindi - Maurya, Arun; Goswami, Sumit; Tyagi, A.k.; Kumar, Ashok; Singh, Mohinder (DESIDOC Journal of Library & Information Technology, 2003)
The article is intended to be a veritable encyclopedia of Hindi websitedevelopment know-how and offers advice on dynamic font creation, embedding,publishing and the related methodology up to their pros and cons. It is one-step guide for the Hindi website development. It provides comprehensive instructions and real world examples, for special coverage of the topics on Hindi website designing and offers advice for developing a truly dynamic Hindi website, on parallel lines to which any multilingual website can be developed. This article is of interest to web developers interested in building dynamic, interactive Hindi websites and for those who are looking for a quick, effective way to build embedded fonts for the web. http://dx.doi.org/10.14429/dbit.22.2.3556